2021
DOI: 10.3390/nu13072191
|View full text |Cite
|
Sign up to set email alerts
|

Konjac Glucomannan Attenuated Triglyceride Metabolism during Rice Gruel Tolerance Test

Abstract: In a recent study, we showed that konjac glucomannan (KGM) inhibits rice gruel-induced postprandial increases in plasma glucose and insulin levels. To extend this research, we investigated the effects of KGM addition to rice gruel on pre- and postprandial concentrations of circulating lipoprotein lipase (LPL), glycosylphosphatidylinositol-anchored high-density lipoprotein-binding protein 1 (GPIHBP1), hepatic triglyceride lipase (HTGL), free fatty acids (FFA), and triglycerides (TG). A total of 13 Japanese men,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[ 4,13–15 ] In addition, recent studies have revealed that prebiotics konjac glucomannan oligosaccharides (KGMO) helps regulate the gut microbiota and enhances mucosal barrier function and anti‐inflammatory status. [ 16–18 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4,13–15 ] In addition, recent studies have revealed that prebiotics konjac glucomannan oligosaccharides (KGMO) helps regulate the gut microbiota and enhances mucosal barrier function and anti‐inflammatory status. [ 16–18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4,[13][14][15] In addition, recent studies have revealed that prebiotics konjac glucomannan oligosaccharides (KGMO) helps regulate the gut microbiota and enhances mucosal barrier function and antiinflammatory status. [16][17][18] With this in mind, we creatively prepared a newly synbiotic combination consisting of two probiotic strains (L. acidophilus and B. infantis), along with one prebiotic KGMO. Consequently, the study aimed to investigate the anti-obesity effects of synbiotic combination, as well as its roles in regulating the intestinal flora maintaining intestinal integrity, alleviate inflammation, and regulating lipid metabolism the mouse model of high fat diet (HFD)induced obesity.…”
Section: Introductionmentioning
confidence: 99%
“…5 Management of metabolic syndrome typically involves lifestyle modifications and pharmacotherapeutic drugs to address hyperglycemia, hypertension, and dyslipidemia. 6 Another approach to reducing the risk of metabolic syndrome is using porang glucomannan. However, research on the effects of porang glucomannan on metabolic syndrome is still limited, necessitating further research to validate its potential impact on body weight, intraperitoneal fat, fasting blood glucose, and GLUT-4 levels.…”
mentioning
confidence: 99%
“…These soluble and thick characteristics challenge digestive enzymes, resulting in a slower gastric emptying rate and inhibiting fat absorption in the small intestine. 6 This makes porang glucomannan an effective component for weight management. Porang glucomannan, also known as Amorphophallus muelleri Blume, is an indigenous tuber commonly found in Indonesia.…”
mentioning
confidence: 99%